1987
DOI: 10.1530/jrf.0.0790589
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative analysis of Sertoli cells in neonatally oestrogen-treated rats

Abstract: Summary. On Day 1 of age rats were treated with 500 \g=m\g oestradiol benzoate.Oestrogen-treated rats had increased numbers of Sertoli cells per reference area or volume, whereas the total number of cells per testis was unchanged. The mean nuclear size was significantly smaller in oestrogen-treated rats than in control rats, at 22 and 45 days of age. The volume density of the heterochromatin clumps decreased from 22 to 45 days of age in control rats (68% fall), the decrease being slower in oestrogenized animal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

1990
1990
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…9). Although changes in testicular morphology and function after neonatal exposure to estrogenic compounds have been well-characterized [10,11,35,45], little attention has been paid to molecular events in the rat testis after prenatal estronization. We examined the changes of testicular expression of ERα and β genes in this experimental model.…”
Section: Discussionmentioning
confidence: 99%
“…9). Although changes in testicular morphology and function after neonatal exposure to estrogenic compounds have been well-characterized [10,11,35,45], little attention has been paid to molecular events in the rat testis after prenatal estronization. We examined the changes of testicular expression of ERα and β genes in this experimental model.…”
Section: Discussionmentioning
confidence: 99%
“…Adult male rats treated with oestradiol on the first day of life show atrophy of the testes and sexual accessory glands (Kind, Folch, Maqueo et al 1965; Aguilar, Tejero, Vaticón & Fernandez-Galaz, 1984), impaired maturation of germ cells (Dhar & Setty, 1976; and of Sertoli and Leydig cells (Gaytan, Pinilla, Aguilar et al 1986;Gaytan & Aguilar, 1987) and decreased serum testosterone concentrations (Frick, Chang & Kind, 1969;Pinilla, Cocconi, Zoppi & Martini, 1989).…”
Section: Introductionmentioning
confidence: 99%
“…Sharpe et al (1998) showed in their study that the number of Sertoli cells per testis was reduced by 40%. On the other hand, there are reports showing that the number was unchanged (Gaytan et al, 1986;Gaytan and Aguilar, 1987). In their studies, Gaytan and colleagues treated day 1 male rats with a single administration of 500 g of estradiol benzoate per rat.…”
Section: Discussionmentioning
confidence: 99%